Bacteriological, Physical And Chemical Properties Of The Pagla Sewage Treatment Plants Water - Saha, Mihir Lal; Alam, Ashraful; Khan, Mahbubar Rahman; Hoque, Sirajul (Dhaka University Journal of Biological Sciences, 2012)
Samples from Pagla sewage treatment plant at different treatment stages showed more or less similar temperature (26.9 - 27.5°C). The pH ranged from 7.2 - 7.9. Influent water and primary sedimentation tank water were brownish in colour while sludge water was light black. The lagoon water and treated water were greenish. The ammonium?nitrogen (NH+4-N) and nitrate?nitrogen (NO-3?N) ranged from 5.24 - 61.94 mg/l and 2.55 - 11.02 mg/l, respectively. Phosphorus of the water was 1.34 - 4.50 mg/l. The suspended solids (SS) ranged from 25.48 ? 374.69 mg/l. In the present study the amount of SS in the treated water were found to be quite satisfactory. The total bacterial population in Pagla sewage treatments plant was in between 2.9 × 104 and 2.5 × 106 cfu/ml. The qualitative bacterial spectrum showed a potential consortium of bacteria associated with the treatment plant. Both Gram positive and Gram negative bacteria were present. Gram positive bacteria were represented by the different species of the genus Bacillus, Aureobacterium and Kurthia. Among them Bacillus was the dominant genus. The different species of Bacillus were Bacillus sphaericus, B. fastidiosus, B. circulans and B. pasteurii. Gram negative bacteria were Zoogloea, Yersinia, Citrobacter and Pseudomonas. A good number of microorganisms were found to be associated with the bio-oxidation of the organic compounds of the influent. The Zoogloea along with other free flowing aerobic heterotrophic bacteria like Bacillus, Pseudomonas could play the major role in the sewage treatment. DOI: http://dx.doi.org/10.3329/dujbs.v21i1.9739 DUJBS 2012 21(1): 1-7